Proleptic and Sylleptic Shoot Formation Is Affected by Rootstock Genotype in Two-Year-Old Branches of Almond Trees - Álvaro Montesinos; Jérôme Grimplet; María José Rubio-Cabetas (Agronomy, 2022)
The implementation of new planting systems in almond (Prunus amygdalus (L.) Batsch, syn P. dulcis (Mill.)) orchards for more sustainable practices has made tree architecture increasingly relevant as an important selection trait in plant breeding. Multiple features define the three-dimensional structure of the tree, with shoot production being the most important. Shoots can develop after a period of rest (proleptic shoots) or immediately (sylleptic shoots), at the same time as the extension of the parent shoot. Scion/rootstock interactions may change the proportion of proleptic and sylleptic shoots and thus alter tree architecture. To study this effect, we analyzed shoot formation on three almond scion cultivars grafted onto five interspecific hybrid rootstocks. The type of shoot (proleptic or sylleptic) and internode number per shoot were collected for two-year-old branches on three-year-old unpruned trees. We found that rootstock genotypes can alter the pattern of shoot production, especially the number of sylleptic shoots formed. More information on the molecular response is needed to comprehend the biological processes behind these differential phenotypes, which appear to be modulated by both apical dominance and apical control.